Farmers perception of rice production community enterprises roles: evidence from Chachoengsao Province, Thailand - H J Cavite; S Suwanmaneepong (My University, 2021)
Abstract Rice production community enterprises (RPCEs) have emerged in Thailand as a group initiative supported by the government to help address the challenges of rice farmers in rural areas. However, farmers still faced problems due to a lack of targeted programs and policies to improve the enterprise’s roles in the community. This study investigated farmer-members’ perception of an RPCE’s specific roles. Primary data were collected through a structured questionnaire administered to 201 farmers in Sanam Chai Khet District, Chachoengsao Province, Thailand. Data were analyzed using the weighted average index (WAI) method to assess the farmers’ perception of the RPCE’s roles. Results reveal that RPCE members have a strong perception of the enterprise’s role in increasing their income. Other roles such as knowledge and skills improvement, supplying inputs at a fair price, increasing social network, product competition with rivals, and provision of credit facilities, were rated as medium, demonstrating the considerable efforts exerted by RPCEs to improving its members. Moreover, a weak rating was given by members for the enterprise’s role as a saving source implying that government should further intensify its support for RPCEs in terms of promoting the saving behavior among members. This study suggests that stronger policy support should be given to upgrade RPCEs based on how members perceived them. This would encourage more member participation and secure more benefits and income for members of the community enterprise.
Keywords: Social enterprise; Global trade, sustainability, and social impact